An ethnography of journalistic production – case studies of the Brazilian press - Travancas, Isabel (Brazilian journalism research, 2010)
In the present article, my objective is to discuss the production of news based upon ethnographic research that I undertook in Brazilian newsrooms. Journalists have their routines determined by the process of confirming, writing about and divulging information. At this moment in which journalism is undergoing far-reaching transformations, it is more important than ever that we discuss how news is made and according to what criteria. Here I analyze a major print newspaper, O Globo and the televised news program Jornal Nacional. I point out the similarities and difference between the professional practices of journalists working in these two media forms. Television has a structure and a form of functioning that is quite particular, as well as a more intense rhythm and relationship to imagery than is the case of newspapers. Newspapers, on the other hand, have similar organizations and routines, presenting information that is almost identical from one newspaper to another, even when there is much competition between them.